DEVELOPMENT OF SIGIL BASED E-BOOK AS MEDIA FOR “TECHNOLOGY AND INFORMATION FOR HISTORY LEARNING” COURSE (Paramita: Historical Studies Journal, 2017)
Nowadays, information and communication technology has been accelerated. This condition also influence on the shift of students attitude toward knowledge and education. Therefore, teacher or lecturer must be creative to deal with this digital generation, for example by developing engaging media. This attempt become more and more important to do especially on history learning since many students considers this subject as dull and meaningless. This research tries to develop an engaging history learning media by using sigil software. The method used in this research is following Sadiman’s model in media development which consist of several stages (1) identification of needs, (2) intention analysis, (3) content development (4) formulating of success measuring instrument, (5) media script writing, (6) validation, (7) revision, and (8) production . From the analysis, it can be inferred that the sigil based e-book with MindMaple content is valid. The percentage of media expert validation is 86%, media expert validation is 85% and small group trial is 96,25%. Therefore this media is feasible to use in the “Technology and Information for History Learning” course. The advantages of this e-book are low cost, easy to use, and engaging. Perkembangan teknologi dan komunikasi telah mengalami akselerasi akhir-akhir ini. Kondisi ini juga berpengaruh terhadap perubahan sikap siswa atau mahasiswa mengenai pendidikan dan pengetahuan. Oleh karenanya, guru dan dosen harus kreatif dalam menghadapi generasi digital. Usaha ini penting untuk dilakukan mengingat pembelajaran sejarah seringkali dianggap membosankan dan tidak bermakna. Penelitian ini berusaha untk mengembangkan media pembelajaran sejarah yang menarik dengan menggunakan perangkat lunak sigil. Penelitian ini menggunakan model pengembangan dari Sadiman yang terdiri atas beberapa tahap (1) identifikasi kebutuhan, (2) analisis tujuan, (3) pengembangan materi, (4) penyusunan instrumen pengukur keberhasilan, (5) penulisan instrumen pengukur keberhasilan, (6) validasi, (7) revisi, dan (8) produksi. Berdasarkan analisis yang dilakukan dapat disimpulkan bahwa e-book berbasis sigil dengan materi MindMaple valid. Percentase dari ahli media adalah 86%, validasi ahli materi 85%, dan uji coba kelompok kecil 96,25%. Oleh karenanya media ini layak untuk digunakan dalam Matakuliah Teknologi Informasi untuk Pembelajaran Sejarah. Kelebihan dari e-book ini adalah murah, mudah digunakan, dan menarik.